Pengaruh Waktu terhadap Kestabilan Nanopartikel Emas yang Disintesis Menggunakan Ekstrak Air Daun Jati (Tectona Grandis) Termodifikasi Mercaptopropionic Acid (MPA) - Yasser, M; Widiyanti, Setyo Erna (Politeknik Negeri Ujung Pandang, 2019)
Gold nanoparticles were synthesized using teak leaf water extract modified with Mercaptopropionic Acid (MPA). The observations for 6 days using UV-Vis spectroscopy, obtained stable gold nanoparticles which were characterized by the maximum wavelength absorption produced in the range of 538.5 nm - 541 nm.